Development of a Cashier Business Transaction System using the Android Based Agile Method - Junanda, David Bagus; Mardhiyyah, Rodhiyah (JISA(Jurnal Informatika dan Sains), 2024)
The grocery retail sector in Indonesia plays an important role in meeting people's basic needs, with grocery merchants in urban and rural areas serving as the main middlemen in the distribution of staples to end consumers. Grocery merchants in Indonesia often face challenges in improving sales efficiency due to the use of conventional methods that are slow, unstructured, and prone to recording errors. These challenges can potentially lead to loss of customers, financial losses, and hinder business growth. This research aims to develop an Android-based cashier application specifically designed for grocery merchants to improve transaction efficiency and stock management. Using a qualitative approach, in-depth interviews were conducted to understand the needs and constraints faced by merchants in the transaction process. The findings were used to design the main features of the application, such as CRUD-based item management (Create, Read, Update, Delete), barcode scanning with a smartphone camera, digital receipt sending via WhatsApp, and payment support via QRIS E-wallet and cash transactions. This application is assumed to be used on Android devices with adequate internet access. The results show that this application is able to reduce recording errors, speed up transactions, and increase customer satisfaction compared to the manual method. The solution is expected to improve productivity, drive business growth, service quality and customer satisfaction as well as the competitiveness of grocers in the digital era. Future recommendations include the development of analytics features to monitor sales performance and support strategic decision-making.